Fostering student agency and motivation: co-creation of a rubric for self-evaluation in an ungraded course - Stranford, Sharon A. (Frontiers in Education, 2024)
No one enjoys grading, neither instructors nor students. The idea is that grades provide the required incentive to learn and act as an "objective" form of evaluation. This view is especially prevalent in STEM, where practitioners pride themselves in quantitative and objective measurements. However, the science of learning tells us that grades and ranking increases competition and stress, pushing learners to engage in tasks regardless of their effectiveness. Grades have been shown to suppress interest in learning, incentivize engagement in easier tasks, and produce shallower thinking. If wanting to learn is something students and faculty can agree on, how do we get there without grading? From psychology research, we know that feedback, separated from grades, along with opportunities to reattempt work without negative consequence, are powerful drivers of the intrinsic motivation to learn. In fact, feedback loops -trying something new, getting feedback, and making changes based on feedback so that you can try again -are a known developmental pathway to authentic learning.In this article, I describe an experiment with a form of ungrading that involves students in the co-creation of selfassessment criteria. The goal is to create learning feedback loops, incentivize learning for learning's sake, and give students some agency in the process of evaluation. This was conducted in an upper division Immunology course at a small liberal arts college. This paper outlines an iterative and dialogical process between students and instructional staff to craft a holistic set of criteria for the evaluation of learning. These criteria became the foundation for regular one-on-one conversations with students and a means to track progress over the semester. End-of-semester student feedback was overwhelmingly positive, citing increased motivation to learn, lower levels of anxiety, a less competitive environment, and growth as a learner. Among the few disadvantages cited were anxieties from grade ambiguity, fears about the process, and extra time, especially for the instructor. This paper highlights the ways in which this system aligns with psychosocial theories of learning, fostering an intrinsic